Tandem non-polymerizing strategy to higher order acrylamide oligomers; potential intermediates for conformational correlations of poly-N-acrylamides - Kendhale, Amol M.; Rajamohanan, Pattuparampil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2008)
This letter describes an efficient tandem non-polymerization strategy to deliver higher order N-acrylamide oligomers. These oligomers, accessible in an one-pot procedure, are potential intermediates for the correlation of stereochemistry (tacticity) with conformation and hydrogen bonding propensities in poly (oligo) N-acrylamides.

Novel foldamer structural architecture from cofacial aromatic building blocks - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, Pattuparampil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2009)
This communication demonstrates the utility of peri-substituted 1,8-diphenylnaphthalene as an effective building block for the construction of novel conformationally ordered synthetic oligomers displaying cofacial structural features.

Synthesis and structural characterization of homochiral homo-oligomers of cis-gamma-methoxy-substituted cis- and trans-furanoid-beta-amino acids - Giri, Awadut G.; Jogdand, Ganesh F.; Rajamohanan, Pattuparampil R.; Pandey, Sunil K.; Ramana, Chepuri V. (European Journal of Organic Chemistry, 2012)
Herein we describe the synthesis of cis-/trans-3-aminotetrahydrofuran-2-carboxylic acids (cis-/trans-FAA) having a ?-methoxy group cis to the amine. The homo-oligomers of these two diastereomeric FAAs have been prepared. Preliminary investigation of their solution secondary structures revealed that they are the same as the homo-oligomers of the parent cis-/trans-FAA with the methoxy group only being a spectator substituent.
Keywords: Amino acids; helical structures; Oxygen heterocycles; Peptides